Soviet legacy is still pervasive in health policy and systems research in the post-Soviet states - George Gotsadze; Akaki Zoidze (Sax Institute, 2021)
Objectives: We examine how health policy and systems research (HPSR) is produced and funded in 14 post-Soviet states to inform possible strategies to improve the supply and quality of research and advance evidence-based health policy making in these states. Study type: Mixed methods. Methods: Using mixed methods - secondary data analysis, desk review and in-depth interviews - this qualitative study is exploratory and explanatory.The secondary data analysis involved a comparative analysis of available data from: a) the 'fiscal space' (national economic resources) - using gross domestic expenditure on research and development for the years 2013-2018; and b) capacity for HPSR - using the number of published papers and average citation per paper (as a quality proxy) in the years 2015-2019. To explain the secondary data analysis findings, we used the approach proposed by Hallerberg et al., highlighting the importance of institutional context, actors, and their incentives and influence in budget allocation decisions. The desk review of available documents and 32 in-depth interviews were conducted remotely to obtain insights on the context and actors. The interview transcripts were analysed using Nvivo 12 software with an inductive approach. Results: In all studied countries, except the Baltic states, funding levels for HPSR remain inadequate. Most research and development funding is allocated to fundamental sciences and biomedical research - fields with more influential long-standing institutional legacies. The low volume and poor quality of published HPSR research appears to be adversely affecting the credibility of researchers in this field in the eyes of critical beneficiaries - policy makers, who do not prioritise and advocate for funding of HPSR. Conclusions: HPSR funding in most post-Soviet countries is caught in a vicious cycle of inadequate funding and poor quality. International collaborative projects focused on post-Soviet states and involving science funders, academic institutions and researchers from those countries may help strengthen HPSR capacity, improve research quality and help boost priority funding and the credibility of researchers in this field.